Pengaruh Sistem Keuangan Desa (SISKEUDES) Terhadap Kinerja Pemerintah Desa Di Kecamatan Doreng - Lastiana Felisitas; Wilhelmina Mitan; Fransiscus De Romario (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to find out whether the Village Financial System influences the Performance of the Village Government in Doreng District. This research uses a quantitative approach with descriptive and associative research. The population in this study was 30 people with the research sample using a saturated sample. The data used in this research is primary data. The data collection technique in this research uses a questionnaire. The data analysis techniques used in this research are descriptive statistical analysis, data quality test, classical assumption test, simple linear regression analysis, coefficient of determination, and t test using IBM SPSS Statistics 26. The results of the descriptive analysis show that the respondents' perceptions of the Village Financial System variable (X) is 90% with very good criteria. Meanwhile, the respondent's perception of the Village Government Performance variable (Y) was 86% in the very good category. The research results show that the Village Financial System variable has a significant value of 0.000 which is smaller than the α value (0.05), so Ha is accepted. Thus, the Village Financial System variable partially influences the performance of the Village Government in Doreng District.